INFLUENCE ON CAPITAL STRUCTURE, PROFITABILITY, AND OPERATING COSTS ON CORPORATE INCOME TAX PAYABLE IN PHARMACY SUB-SECTOR COMPANY REGISTERED IN INDONESIA STOCK EXCHANGE - Oktaviani, Vina; Lestari, Dini Martinda; Afriani, Raden Irna (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
Corporate income tax payable fluctuates, and therefore, corporate income tax payable in Indonesia is in a state of national economic recovery, and corporate income tax rates are decreasing. This study aims to determine the influence of Capital Structure, Profitability and Operating Costs on Corporate Income Tax Payable in Pharmaceutical Sub-Sector Companies Listed on the IDX for 2019-2023. The research method used is an associative method with a quantitative approach. The population in this study is pharmaceutical subsector companies listed on the IDX for the 2019-2023 period. The sampling technique used is purposive sampling, so the samples obtained were seven companies and 5 years of observation. The analysis used was classical assumption test, multiple linear regression analysis, and hypothesis testing. The results of this study state that the capital structure variable (X1) obtained a cal value = |-2.457| > ttable = 2.039 with a significant level of 0.020 < 0.05, then H0 was rejected, and H1 was accepted, the profitability variable (X2) was obtained a cal value = 4.065 > ttable = 2.039 with a significant level of 0.000 < 0.05, then H0 was rejected, and H2 was accepted, and the operational cost variable (X3) was obtained a tcal value = |-2.875| > ttable = 2.039 with a significant level by 0.007 < 0.05, then H0 is rejected and H3 is accepted. Simultaneously, the value of Fcal was obtained at 11.175 > 2.91 Ftable and significant for LDAR, ROA and Operating Costs, was 0.000 or less than 0.05, then Ho was rejected, and Ha was accepted. The conclusion of this study shows that capital structure, profitability, and operational costs affect Corporate Income Tax Payable simultaneously